2020
DOI: 10.3390/ijerph17186466
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental and Social Responsibility on Customer Loyalty: A Multigroup Analysis among Generations X and Y

Abstract: The purpose of the current study was to comparatively estimate, for generation X and generation Y, the impact of corporate environmental and social responsibility on customer loyalty, via customer–company identification and customer satisfaction as mediators. For this, a survey was conducted among a sample of telecom customers, comprising 445 members of generation X, and 601 of generation Y. Data were analyzed using partial least squares structural equation modeling and multigroup analysis. Results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 89 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…Relevant literatures have confirmed that CSR has a positive effect on customers' loyalty by improving and enhancing company's brand image, customers' satisfactions, trustworthiness, behaviors, organization's longterm marketing strategy and so on, in order to become a strong market leader and snatch more market shares over competitor in the marketplace within same industry sectors. Based on hypothesis 1, we enable to draw a conclusion that environmental responsibility demonstrates a positive impact on customers' loyalty and supported relevant previous studies (Moisescu & Gică, 2020) and (Mohd Suki, 2015) and corroborated a strong influence on customers' loyalty (Liu et al, 2019). In other words, it helps to increase and better customers' loyalty through building good reputation and closer relationship with existing customers and penetrating vaster customer groups, namely Lao Telecom has supported "Good-Things-Project for Lao Society" in mitigating the plastic use, Garbage Collection Project for Clean City and other environmental activities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Relevant literatures have confirmed that CSR has a positive effect on customers' loyalty by improving and enhancing company's brand image, customers' satisfactions, trustworthiness, behaviors, organization's longterm marketing strategy and so on, in order to become a strong market leader and snatch more market shares over competitor in the marketplace within same industry sectors. Based on hypothesis 1, we enable to draw a conclusion that environmental responsibility demonstrates a positive impact on customers' loyalty and supported relevant previous studies (Moisescu & Gică, 2020) and (Mohd Suki, 2015) and corroborated a strong influence on customers' loyalty (Liu et al, 2019). In other words, it helps to increase and better customers' loyalty through building good reputation and closer relationship with existing customers and penetrating vaster customer groups, namely Lao Telecom has supported "Good-Things-Project for Lao Society" in mitigating the plastic use, Garbage Collection Project for Clean City and other environmental activities.…”
Section: Discussionsupporting
confidence: 85%
“…Technical speaking, environmental responsibility is an essential aspect in generating and improving customers' loyalty as well as there is a relationship between two variables. Empirical studies asserted a positive impact of environmental factor on customers' loyalty (Moisescu & Gică, 2020) and also suggested the need to consider other service sectors from developing countries. By way of contrast, another scholar discovered that environmental responsibility was negatively influenced but not statistically significant on customers' loyalty (Dimitriadis & Zilakaki, 2019); the paper also recommended to explore for disparate sectors; while there was a strong influence for the impact of CSR components on Chinese customers' loyalty (Liu et al, 2019); customer environmental satisfactions and environmental friendliness of the company has a statistical significance and positive impact on customer loyalty (Mohd Suki, 2015).…”
Section: The Effects Of Environmental Responsibility On Customers' Loyaltymentioning
confidence: 99%
“…In this context, confronted with various scandals over time (Sádaba et al, 2019), it is necessary for fast fashion retailers to identify how to leverage store attributes and activities for their clients to generate customer satisfaction, and of course, loyalty (Hung et al, 2019). At the same time, they must strive consistently to make customers aware of the fact that despite the potentially negative impact they may have on the environment, they do take socio-environmental responsibility for their actions (Moisescu & Gică, 2020), adopting and implementing within the entire supply chain a sustainability strategy (Iglesias et al, 2020). Resorting to such strategies is increasingly necessary due to consumer awareness of the effects and impact that overconsumption of materials has on the environment and on society Marques et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer loyalty is a prime objective of any organization and in the current business environment, which is already volatile, uncertain, complex, and ambiguous (VUCA), contemporary businesses must develop a competitive advantage on a solid foundation, for example, looking at sustainability as a base for competitive advantage [10][11][12]. Different studies in prior literature have developed a relationship between perceived environmental sustainability and consumer loyalty [13,14], but these studies are inconclusive. For example, in a recent study, Nyadzayo et al [15] confirmed that corporate social responsibility (CSR) has no direct relationship with loyalty in the sports sector.…”
Section: Introductionmentioning
confidence: 99%